Dose-volume relationships of radiation injury to canine lung: early effects - Poulson, Jean Marie, author; Gillette, Edward L., advisor; Orton, E. Christopher, committee member; Powers, Barbara E., committee member; Steyn, Phillip F., committee member (Colorado State University. Libraries, 2001)
Tolerance of lung is a critical limiting factor in radiotherapy of tumors involving the thorax. The influence of volume on radiation tolerance of lung is an effect that has not been adequately quantified. The goal of our studies was to determine the dose-volume relationship of lung injury in normal dogs. A three-dimensional treatment planning system was used to design mediastinal fields of increasing width to irradiate 33%, 67% or 100% of both lungs combined. Radiation was delivered in 1.5 Gy fractions over 6 weeks using x rays from a 6 MV clinical linear accelerator. This study was part of a larger study investigating volume and tolerance-dose relationships for early and late effects in normal canine lung. The early effects reported here were evaluated at 3 months after irradiation. The late effects were evaluated 24 months after irradiation and will be reported elsewhere. No dogs irradiated to 33% of their total lung volume developed severe symptomatic pneumonitis, and a clear volume effect was observed in the 67% and 100% lung volume groups. Serotonin uptake and changes in plain thoracic radiographs were other endpoints demonstrating a volume effect. Other pulmonary function endpoints were evaluated, but were either not sensitive enough to demonstrate a volume effect, considering the great compensatory capacity of normal, nonirradiated lung, or they demonstrated a threshold effect, independent of lung volume irradiated. Radiation injury as assessed by histology was independent of volume irradiated. Volume relationships in lung depend on the endpoint being considered. Volume effects in the lung are consistent with increased morbidity due to the same effect in a larger volume of tissue. Volume effects in the lung are also critically dependent on the compensatory capacity of the nonirradiated lung. Underlying pathophysiology of irradiated tissue, as well as decreased compensatory capacity of nonirradiated tissue may have a strong effect on the dose-volume response. When small volumes of lung are irradiated (33% or less) the dose-limiting complications are more likely to be related to the structural tolerance of vessels or airways rather than loss of pulmonary function.
Keywords: oncology; radiology; medical imaging